1995
DOI: 10.1084/jem.181.4.1557
|View full text |Cite
|
Sign up to set email alerts
|

Novel packages of viral and self-antigens are generated during apoptosis.

Abstract: SummaryImmune context is an essential determinant of the host response to potential autoantigens. The clustering of the autoantigens targeted in systemic lupus erythematosus within surface blebs of apoptotic cells generates high concentrations of autoantigen within discrete subceUular packages. We demonstrate here that when apoptosis is induced by Sindbis virus infection, viral antigens and autoantigens cocluster exclusively in small surface blebs of apoptotic cells. The surface of these blebs is rich in viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
0
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(158 citation statements)
references
References 17 publications
4
150
0
4
Order By: Relevance
“…This generated high concentrations of known autoantigens within discrete subcellular packages. In another study, the same group found that after induction of apoptosis by Sindbis virus infection in HeLa cells, viral antigens and autoantigens cocluster exclusively in small surface blebs of apoptotic cells (42). These blebs form antigenic structures of mixed viral and self origin and could define a novel immune context.…”
mentioning
confidence: 96%
“…This generated high concentrations of known autoantigens within discrete subcellular packages. In another study, the same group found that after induction of apoptosis by Sindbis virus infection in HeLa cells, viral antigens and autoantigens cocluster exclusively in small surface blebs of apoptotic cells (42). These blebs form antigenic structures of mixed viral and self origin and could define a novel immune context.…”
mentioning
confidence: 96%
“…Autoantigens in general have been found to have peculiarities of charge or of secondary structure [16]; or genetic polymorphisms, as in the paper by Stadler et al [5]. Particular autoantigens may have particular features: they may be mimicked by prokaryotic sequences [17]; they may have biological activities such as chemoattraction [18]; they may bind secondary receptors such as TLR9 [19]; they may traffic to apoptotic blebs [20]; they may be cleaved by apoptosis enzymes [21]; or they may undergo posttranslational modifications [22].…”
Section: Autoantigen Selectionmentioning
confidence: 99%
“…Nearly all protein autoantigens recognized by sera of SLE patients contain cleavage sites for caspases or granzyme B. These autoantigens are specifically cleaved during apoptotic or necrotic cell death (40)(41)(42). Therefore, it can be speculated that cryptic epitopes from modified autoantigens (often referred to as altered "self") from apoptotic cells can become dominant, if the epitope hierarchy changes due to proteolysis (43).…”
Section: Apoptosis and Autoimmunitymentioning
confidence: 99%